Evaluation of prenatal vitamin-mineral preparations in the context of recommended dietary supplementation. Are pregnant women supplied with what they should get? - Regina Wierzejska (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. The composition of preparations, intended for pregnant women is an important issue of proper dietary supplementation. The range of such products on the market is very wide and their composition is not regulated by law. Objectives. To evaluate the composition of preparations for pregnant women in the context of 2014 Polish Gynecological Society (PTG) recommendation and the 2020 recommendation of the Polish Society of Gynecologists and Obstetricians (PTGiP). Materials and methods. A range of preparations was collected in pharmacies and e-pharmacies in 2019. The nutrient content was determined based on the information on the unit packaging or the pharmacy's website. The content of folic acid, vitamin D, iodine, DHA, and iron was assessed. Results. There were 33 vitamin-mineral preparations (VMPs) on offer on the analyzed market. All preparations contained folic acid, of which 55% contained precisely the dose recommended by the PTG, and 45% of the preparations is compliant in this respect with the recommendation of the PTGiP. Ninety seven percent of VMPs contained vitamin D. Fifty percent of them did not contain this vitamin at the dose recommended by the PTG, and half of the preparations do not meet the PTGiP recommendation either. Ninety seven percent of VMPs contained iodine. Out of them 44% contained a too low dose of iodine, by the PTG standards, but only 9% of preparations do not meet the PTGiP recommendation in this respect. DHA was a component contained in 73% of VMPs. Among them, 33% contained the dose recommended by the PTG for women who eat little fish and 88% of the preparations are in line with the new recommendation PTGiP. Eighty two percent of preparations contained iron, which in the light of the PTGiP recommendation is debatable. Conclusions. The composition of many VMPs did not reflect experts' recommendations regarding the type and amounts of particular nutrients.